Narrative instability : destabilizing identities, realities, and textualities in contemporary American popular culture - Schubert, Stefan (Doctoral student) (American Studies - A Monograph Series., 2019)
"This book introduces the concept of 'narrative instability' in order to make visible a new trend in contemporary US popular culture, to analyze this trend's poetics, and to scrutinize its textual politics. It identifies those texts as narratively unstable that consciously frustrate and obfuscate the process of narrative understanding and comprehension, challenging their audiences to reconstruct what happened in a text's plot, who its characters are, which of its diagetic worlds are real, or how narrative information is communicated in the first place. Despite - or rather, exactly because of - their confusing and destabilizing tendencies, such texts have attained mainstream commercial popularity in recent years across a variety of media, most prominently in films, video games, and television series. Focusing on three clusters of instability that form around identities, realities, and textualities, the book argues that narratively unstable texts encourage their audiences to engage with the narrative constructedness of their universes, that narratively unstable texts encourage their audiences to engage with the narrative constructedness of their universes, that narrative instability embodies a new facet of popular culture, that it takes place and can only be understood transmedially, and that its textual politics particularly speak to white male, middle-class Americans." -- Back cover.